Status of Collection in Agricultural Libraries of North India with an Overview of the Trend in Acquisition - Bhat, Nazir Ahmad; Ganai, Shabir Ahmad (Journal of Information and Knowledge, 2017)
Purpose: This paper is an attempt to explore the status of collection in Agricultural libraries of North India and assess the impact of the advent of Electronic Information Resources (EIRs) on acquisition. Design/Methodology/Approach: A questionnaire was used as data collection tool to collect data from the University Librarians. Telephonic interaction and e-mail correspondence was also used to clear doubts, remove ambiguities and obtain data from the respondents. Findings: The majority of the agricultural libraries in north India have a sound collection of information resources in print form, which may continue to act as a source of attraction for users in future for a long time to come. Yet the acquisition of information resources in print form across the studied libraries continues at routine pace, and as such the advent of e-resources seems to have not yet had any prominent impact on acquisition of resources in print form. E-Books have not yet been fully incorporated into the library collection and the e-journal collection 'CeRA' seems to meet the needs of users, as no additional e-journals are seen to be subscribed. Research Limitations: Only seven agricultural libraries have been taken as a sample. Moreover, the work is confined to only 2 aspects i.e. current status and the impact of EIRs on acquisition of information resources. Other aspects like that of collection development; storage and accommodation; preservation; library functionality and library services need to be studied as well. Originality/Value - This is the first work of its nature in north India and the findings should help librarians to decide on print and electronic forms of information resources that need to be acquired.